Políticas de formação e trabalho docente : narrativas de professores da escola do campo - Pires, Suely Maria (2014)
This research is linked to the Graduate Program in Education at the Federal University of Mato Grosso - Campus Rondonópolis and was accomplished with the support of the Centre for Education Programme (Programa Observatório da Educação/OBEDUC). In the last decades, have grown the discussions on field education with respect to the claims of better living conditions, education, livelihood and access to the cultural goods of the Brazilian peasant population. This research aimed to investigate the policies that were centered on teachers training from and to the field as well as their performance in this life type. Close to the training, there are the teacher’s practices that are evidenced as productive, in the processes of teaching and learning in this life atmosphere of educational work. Included in the survey experienced teachers and novice teachers graduates who work in the country school, in order to better observe how are assisted in their work by the policies and training for rural education. The subject that mobilized this research is: how beginning teachers who work or have worked in schools in the country analyze education policies a and teaching career and its impact on their daily practice. To develop research, we have appropriated the qualitative approach to the (self) biographical method, adopting the narratives as instruments for data collection. The research was developed in two public schools in the State of Mato Grosso with three subjects. The results showed that existing policies after LDB 9394/96 have turned to the country, although they do not perform yet into affirmative action policies in the analysis of the subjects and teachers who work in this space.